To Determine the Frequency of Different Complex Coronary Lesions in Diabetic Patients - Shahid Iqbal, Ahmad Kamran Khan, Syed Bakht Ruidar, Syed Sardar Rahim, Mirza Nauman Rahi, Ahmed Ali Ishaq Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetic people have an excessive amount of coronary atherosclerosis. Diabetes mellitus is a strong predictor of mortality and MI in both men and women. It’s unclear whether diabetics and non-diabetics have different rates of complicated coronary lesions such bifurcation and ostial lesions. Objective: To find out how often different types of complicated coronary lesions are in diabetic people. Methodology: 136 individuals were enrolled in this study. All patients had coronary angiography using the conventional femoral or radial artery technique. Angiographic data was obtained by two interventional cardiologists with 3 years of post-fellowship experience interpreting angiograms. Data on complicated coronary lesions was collected. It has a significant p-value (0.05), indicating that there is a significant difference in this disorder between the two groups. Results: The mean age of the 136 patients was 47.3±12.2 years (range 25 to 70 years). There were 71 males (52.2%) and 65 females (47.8%). Mean BMI was 25.9±1.3 kg/m2, mean duration of diabetes mellitus was 7.5±3.5 year, mean weight was 75.7±5.1 and mean height was 5.3±0.6 m. Coronary artery lesions were as follows: bifurcation lesions 85 (62.5%), ostial lesion 32 (23.5% and LMCA lesions 19 (14%). Stratification with regard to age, gender, BMI and duration of diabetes was also carried out. Conclusion: In diabetic patients, complicated coronary lesions such as bifurcation and ostial lesions were shown to be substantially more prevalent than LMCA lesions.